Development of WC-Feal Composite by Stir Casting Method - Rahul Verma; Rohit Srivastava (International Journal of Engineering and Management Research, 2019)
In this paper author make an effort to develop a new material for fulfill the need of present requirement. This material is developed by the using of stir casting method. A AMMC’s composite are developed to fulfill the need of present requirements. This composite material is prepared by the use of 3 metals. These metals are iron (Fe), aluminum (Al) and tungsten carbide (WC).Thus this composite come under metal matrix composite. This composite is WC – FeAl composite. This is prepared by the use of stir casting method. The base metals are iron and aluminum. These are having equal quantity by weight. In this the sample is prepared by the change the of percentage reinforcement. This is varying from 0 to 3%. A test is conduct to check their tensile strength as well as compressive strength. By these test it is confirm that with the increase the percentage of reinforcement in the composite their tensile strength is decrease but their compressive strength is increase.